Land Suitability Analysis Using the Modified Profile Matching Method - Pratistha, Indra; Dewi, Ni Wayan Jeri Kusuma (INFOTEKS (Information Technology, Computer and Sciences), 2024)
The plantation sector plays a significant role in Indonesia's economy, particularly in coffee production. In the province of West Nusa Tenggara (NTB), coffee production experienced annual fluctuations from 2018 to 2021. One of the causes is the lack of public understanding in utilizing land according to its natural potential, leading to decreased productivity and land degradation. Based on discussions with plantation experts from Politeknik LPP Yogyakarta, this study identifies land characteristics divided into qualitative data, such as drainage and soil texture, and quantitative data, including temperature, rainfall, humidity, elevation, effective soil depth, slope, cation exchange capacity (CEC), base saturation, pH H2O, organic carbon (C-organic) content, and nitrogen (N). The application of the modified profile matching method demonstrates its capability in providing recommendations for coffee crop suitability in East Lombok Regency. Data matching tests between land profile values and coffee crop profile values, involving experts from Politeknik LPP Yogyakarta and the NTB Provincial Agriculture Office, resulted in liberica coffee being ranked first in eight sub-districts. However, in one sub-district, Sembalun, robusta coffee did not rank second, as arabica coffee was preferred.